Developing motor competency in youths: Perceptions and practices of strength and conditioning coaches - Burton, A. M.; Eisenmann, J. C.; Cowburn, I.; Lloyd, R. S.; Till, K. (Journal of Sports Sciences, 2021)
Motor competency is integral to the long-term athletic development of youths. Strength and conditioning (S&C) coaches are recommended to deliver motor competency interventions, yet no studies have investigated their perceptions and practices for developing motor competency in youths. Sixty-seven male, and 4 female S&C coaches completed an initial and follow up questionnaire using a 5-point Likert scale, rating 1] the importance of developing competence, and 2] how frequently they developed competence across 90 motor competencies. Over 55% of S&C coaches reported a broad range of "important" (69/90) and "frequently developed" (48/90) motor competencies. The most important motor competency was "deceleration" (4.9 ± 0.3), whilst "hip hinge (bilateral)" was the most practised (4.4 ± 0.5). S&C coaches targeted upper body pushing and pulling competencies more than their perceived importance, whilst agility (e.g., turning) competencies were targeted less than their importance. Further analysis showed S&C coaches who delivered 3-4 sessions per week targeted 15-18% more competencies compared to = 2 sessions per week. Overall, these findings have strong implications for youth motor competency development including the reflection of important vs. practised competencies, coach education programmes, and consideration for how S&C coaches should seek to optimise motor competency development within youths.